Exploring motivations of social media influencers as an emerging job market - Chongmi An; Jony Oktavian Haryanto (President University, 2021)
The study explores the motivations of female Social Media Influencers (SMIs) in Indonesia during the Covid-19 pandemic. Phenomenological inquiry is adopted to capture the lived experience of the six Instagram SMIs. Two major themes emerge from the findings; 1) SMIs approach Instagram as a portfolio to showcase their values, hobbies and careers and 2) SMIs increasingly perceive Instagram as a source of income, where being SMI is a job rather than a hobby and endorsement as their main job task. In context of self-determination theory, SMI motivations are built on several intrinsic and extrinsic motives and the net value (Intrinsic minus extrinsic) correlates to authenticity of the SMI and their endorsements.